Spanish Fascist Women's Transnational Relations during the Second World War: Between Ideology and Realpolitik. (October 2019) - Morant i Ariño, Toni
Spanish fascist women played a very active role in the Falange's cross-border relations with Nazi Germany and Fascist Italy during the Spanish Civil War and the Second World War. From the very beginning, fascist women took a preeminent place in these contacts and exchanges in order to see with their own eyes how both fascist models were at a practical level. These relationships between fascist women's organizations were born out of deep ideological affinity and were especially fluid, firstly on a bilateral level and after 1940 on the 'New Order' Europe-wide multilateral, transnational collaboration. However, they lacked neither of political calculation nor could abstract from the wider frame of international politics in such an eminently war period. As this article will show, Falangist women used these fluid but less studied relationships to consolidate their own political position at home and explore other ways of political participation in a Nazi-Fascist New Europe, while at the same time trying to secure there a pre-eminent place for non-belligerent Spain. In the end, concerns about the own survival of the Franco dictatorship as the fate of war clearly changed in 1943, let ideological affinity succumb to the diplomatic conveniences they had once meant to overcome.